Gut microbiota and lipopolysaccharide content of the diet influence development of regulatory T cells: studies in germ-free mice - Hrncir, Tomas; Stepankova, Renata; Kozakova, Hana; Hudcovic, Tomas; Tlaskalova-Hogenova, Helena (BMC immunology, 2008)
BACKGROUND: Mammals are essentially born germ-free but the epithelial surfaces are promptly colonized by astounding numbers of bacteria soon after birth. The most extensive microbial community is harbored by the distal intestine. The gut microbiota outnumber ~10 times the total number of our somatic and germ cells. The host-microbiota relationship has evolved to become mutually beneficial. Studies in germ-free mice have shown that gut microbiota play a crucial role in the development of the immune system. The principal aim of the present study was to elucidate whether the presence of gut microbiota and the quality of a sterile diet containing various amounts of bacterial contaminants, measured by lipopolysaccharide (LPS) content, can influence maturation of the immune system in gnotobiotic mice. RESULTS: We have found that the presence of gut microbiota and to a lesser extent also the LPS-rich sterile diet drive the expansion of B and T cells in Peyer's patches and mesenteric lymph nodes. The most prominent was the expansion of CD4+ T cells including Foxp3-expressing T cells in mesenteric lymph nodes. Further, we have observed that both the presence of gut microbiota and the LPS-rich sterile diet influence in vitro cytokine profile of spleen cells. Both gut microbiota and LPS-rich diet increase the production of interleukin-12 and decrease the production of interleukin-4. In addition, the presence of gut microbiota increases the production of interleukin-10 and interferon-gamma. CONCLUSION: Our data clearly show that not only live gut microbiota but also microbial components (LPS) contained in sterile diet stimulate the development, expansion and function of the immune system. Finally, we would like to emphasize that the composition of diet should be regularly tested especially in all gnotobiotic models as the LPS content and other microbial components present in the diet may significantly alter the outcome of experiments.
Keywords: gnotobiologické modely; střeva; Immune System; Lipopolysaccharides; Immune Tolerance; Cell Proliferation; Th1 buňky; Germ-Free Life; regulační T-lymfocyty; lipopolysacharidy; cytokiny; Lymphocyte Activation; buněčná diferenciace; myši inbrední BALB C; střevní sliznice; Th1 Cells; aktivace lymfocytů; imunitní systém; dieta; Mice, Inbred BALB C; T-Lymphocytes, Regulatory; Animals; zvířata; Intestinal Mucosa; Th2 Cells; Diet; myši; imunologická tolerance; proliferace buněk; Th2 buňky; Cytokines; Intestines; Mice; Cell Differentiation